Adaptive house design and people’s habits in achieving thermal comfort in Gayo Highland Aceh, Indonesia / Erna Meutia and Laina Hilma Sari - Meutia, Erna; Hilma Sari, Laina (Universiti Teknologi MARA, Perak, 2021)
The Gayo Highland is one of the districts in Aceh Province, Sumatra. Due to the topography, this area has a lower temperature compared than the flat and coastal areas in Aceh. The thermal comfort that is felt is based on a person's mental condition and how he expresses his satisfaction with his thermal environment. In other words, it shows how humans adapt to their thermal environment. Thermal comfort based on human adaptation is known as adaptive thermal comfort. The form of dwelling for the Gayo Highland community has shifted and changed from traditional dwelling to Transitional and Modern forms that influence the Gayo Highland community's adaptation to achieve thermal comfort. Therefore, this paper aims to investigate the house design in Gayo highland in providing warmth to the occupants naturally in the cold environment. Another aim of this study is to investigate the people's habits in warming up the body to deal with the low air temperature in the area. This study shows how the local people adapt themselves through the house element and daily habit to gain the internal thermal comfort.